Vitamin content and MDA levels of certain white grape varieties from different altitudes in Turkey - Akbaba, Emel; Aydin, Sevinc; Sanyurek, Nesrin Karaca; Cakir, Atilla; Erisir, Figen Erdem (United Arab Emirates Univ, 2023)
Grapevine (Vitis vinifera L.) is regarded as one of the world's most important fruit crops in terms of acreage and commercial worth. Grapes are used to make not only wine but also fresh fruit, dried fruit, and juice. The quality of grapes or wine is significantly affected by environmental factors such as altitude, soil type, and climate. In this study, the 5 white grape varieties (Agin beyazi, Tahannebi, Kabarcik, Silfoni, and Besni) grown at different altitudes (800 m, 1000 m and 1200 m) in Turkey were investigated for their vitamin, and phytosterol concentrations as well as lipid peroxidation content. Silfoni grape harvested at 800 m was found to possess the lowest lipid peroxidation content. High altitudes, were found to reduce lipid peroxidation contents in the Agin beyazi, Tahannebi, and Kabarcik strains. The highest stigmasterol (98.34 pg/g), and beta-sitosterol (86.90 pg/g) concentrations were found within Silfoni grape variety harvested at 800 m. The highest vitamin D-2 and D-3 levels were found in Agin beyazi (1.39 pg/g) and Kabarcik (4.13 pg/g) grape varieties, both harvested at 1200 m. Kabarcik grape, however, revealed the highest concentrations of R-tocopherol (63.09 pg/g) and alpha-tocopherol (24.13 pg/g) at 1200 m within the samples. The highest vitamin K-2 level was determined within the Tahannebi grape (15.44 pg/g) from 1200 m. It was observed that the vitamin and phytosterol concentrations of white grape varieties tended to increase, while the lipid peroxidation values tended to decrease at high altitudes, especially at 1200 m. This study also exhibited a strong relationship among Vitamin D3, R-tocopherol, and alpha-tocopherol in the studied white grape cultivars.
Keywords: Vitis vinifera; White grape; Vitamin; MDA; Altitude